Strategic benchmarking reloaded with six sigma : - Watson, Gregory H. (John Wiley & Sons, 2007)
Stimulating business improvement with benchmarking. Linking Six Sigma to strategic planning and benchmarking. Understanding the essence of process benchmarking. Making statistical comparisons in benchmarking. Applying benchmarking results for maximum utility. Reviewing lessons learned from old case studies. Conducting a strategic benchmarking study. Performing an operational benchmarking study. Mainstreaming benchmarking into strategic planning. Creating a sustainable benchmarking capability. Plus: appendices covering the benchmarking code of conduct, operating procedures, and Web resources